A democracia deliberativa atando e desatando nós nas políticas educacionais: por um inglês inclusivo - Correa, Leonardo Neves (2022)
The ascension of Libras (Brazilian Sign Language) in 2002 as an official language on the national territory provided, among other things, greater visibility to the deaf community. In the field of education, topics such as special educational policies and specific pedagogies for teaching deaf people have gained greater prominence in research on teacher education. Theoretical background: The area of Applied Linguistics (AL), in particular the sub-area of foreign language teaching education, has increased the number of research on the (still incipient) issue of the teaching of English to deaf students in mainstreamed contexts. Although we can observe a progressive increase in research that problematizes the issue in specialized literature, the same is not true when it comes to educational linguistic policies. Without an explicit policy, the topic runs the risk of remaining neglected in the areas of initial and continuing education. In this context, this study aimed at fostering the creation and/or proposition of public policies for the teaching of English to the deaf in contexts of inclusive mainstream education, based on the contribution of those who experience this context in their daily lives, more specifically: i ) deaf or hard of hearing people; ii) English teachers; iii) and Libras interpreters. The research proposal which aimed at setting a public agenda on the referred topic was based on studies on “democratic practices” developed by Matthews (2006; 2014). This participatory action research (REASON & BRADBURY, 2001) of exploratory nature was developed in two cycles, based on the aforementioned democratic practices: I) Identification of the problem; II) Framework for deliberation; Phase I data of the project were collected from semi-structured interviews in the format of focus groups and one-on-one interviews; then, these data were analyzed in the light of Content Analysis (BARDIN, 1977). As a result, one can observe an inclination towards propositions of actions that are linked to one of the following areas: 1. Professional training and adequate working conditions for Libras interpreters and teachers of English; 2. Cognitive and cultural development of deaf students in regular schools; 3. School community awareness and engagement for the inclusion of students with disabilities. Based on these three propositions, a deliberative discussion guide was compiled, based on the framework proposed by Rourke (2015). The guide aims to encourage schools and other stakeholders to hold public forums and deliberate on the issue in order to identify alternatives that respond to local needs. The guide featuring a post-forum survey are presented as open-source products of this research. It is hoped that the results of these discussions can inform the writing of inclusive policies for the teaching of English in mainstreamed contexts